P123 Type I collagen degradation fragments and type IV collagen formation/degradation ratio are serological biomarkers for stricturing (Montreal B2) Crohn's disease. (27th May 2021) - Bourgonje, A R; Alexdottir, M; Loveikyte, R; Bay-Jensen, A C; van Dullemen, H M; Visschedijk, M C; Festen, E A M; Weersma, R K; Karsdal, M A; Faber, K N; Mortensen, J H; Dijkstra, G
Abstract: Background: Crohn's disease (CD) is characterized by increased extracellular matrix (ECM) remodeling, which is a key pathophysiological mechanism underlying intestinal stricture formation and other fibrotic disease complications. Alterations in intestinal ECM turnover may be reflected by products of collagen formation and degradation that are released into the systemic circulation. In this study, we aimed to investigate associations between serological biomarkers of collagen turnover and disease behavior subtypes according to the Montreal classification in patients with CD. Methods: Serological biomarkers of collagen formation (PRO-C3, PRO-C4) and matrix metalloproteinase (MMP)-mediated collagen degradation (reC1M, C3M, C4M, C4G, C6Ma3) were measured using neo-epitope solid-phase competitive enzyme-linked immunosorbent assay (ELISA) technology in 101 patients with CD (Montreal B1: n =47; B2: n =28; B3: n =26) who were characterized according to the Montreal classification. Logistic regression modelling and receiver operating characteristics (ROC) statistics were used to assess discriminative power. Results: Specific fragments of MMP-2, 9, 13-mediated degradation of type I collagen (reC1M) were significantly reduced in patients with stricturing (Montreal B2) disease compared to other disease phenotypes (B1 and B3) ( P <0.001). Ratios of type IV collagen formation and degradation (PRO-C4/C4M) were significantly elevated in Montreal B2 patients ( P <0.001). No differences in remaining serological biomarkers were observed between the different Montreal subtypes. Both reC1M and PRO-C4/C4M ratios demonstrated high discriminative power to distinguish inflammatory CD (B1) from stricturing (B2) CD, also after adjustment for confounding factors (area under the curve [AUC] 0.85 and 0.84, respectively). Conclusion: Elevated degradation of type I collagen and excessive (relative) formation of type IV collagen strongly associate with stricturing CD (Montreal B2) and accurately discriminate it from inflammatory CD (Montreal B1). Therefore, reC1M and PRO-C4/C4M ratios could serve as serological biomarkers for stricturing CD. Our results should be validated in additional prospective, larger patient cohorts to corroborate these findings.